Insights into the structural, electronic and magnetic properties of gold clusters: Comparison between Au12Cr and Au12Mo clusters - Lan, Ngo Thi; Nguyen, Van Dang; Nguyen, Thi Mai; Phung, Thi Thu; Phan, Thanh Phuong; Tran, Xuan Quy; Le, Thi Tuyet Ngan; Nguyen, Thi Dung; Nguyen, Thanh Tung (Communications in Physics, 2024)
Modification of the chemical and physical properties with respect to element component in atomic clusters has paved the way for great potential in both fundamental study and applications. An investigation on the structure, stability and magnetic properties of gold clusters doped by Cr and Mo (Au12Cr and Au12Mo) is discussed in this work, using the density functional theory calculation. The bond strength of AuM dimers governs the globally minimum structural evolution in the Au12M clusters, which can be classified into two principal forms: the icosahedral (Mo dopant) and the cone-like structures (Cr dopant). The average binding and dissociation energies indicate that the enhanced stability of cluster stem from the contribution of Cr/Mo atom. The molecular orbital (MO) diagram and the spin distribution are computed to better understand the electronic configuration and magnetic behavior of the studies clusters. The Au12Cr has a significant magnetic moment of 4 µB. Conversely, the magnetic moment is completely quenched in Au12Mo cluster. Furthermore, the IR spectra of Au12M are also predicted.